Technological artifacts and their relationship with science, technology, society, the environment and their contribution to the company (Revista "Boletín el Conuco", 2021)
This article is the product of the research work that was developed in the framework of the in- terinstitutional doctorate in education, aims to contribute to the search of the relation of the technological artifacts with the science, the tech- nology, the Society, the environment and its con- tribution to the company.The findings seek from the question: Is it possi- ble to do archaeology to technological artifacts to reveal the relations that it has with science, te- chnology, society, the Environment and the com- pany, to generate a strategy for the learning of the Technology and the literacy of human talent? The working hypothesis on this question is affir- mative and it is proposed that the artifacts being the result of a technological and social process they can reveal such relationships of concepts. From this assumption, the discourse plays a deci- sive role in the qualification of the subjects. The methodology used, will allow to establish that the contributions of the theory of the discour- se Help to organize an archaeological method to observe the technological artifacts or more specifically what the hermeneutics can make as a method.
Keywords: Archaeology, technological artifact, science, technology, society, Environment, company